Using Active Learning Classrooms in Building an Infrastructure for Access to Research Data - Ekman, Stefan; Francke, Helena (Septentrio Conference Series, 2018)
Watch the VIDEO. As a central part of its work towards Open Science, Sweden is building an infrastructure for managing, storing, and providing access to research data. A vital component of this infrastructure will be functions at Swedish universities for supporting researchers with data access and management. To support these local functions, here referred to as Data Access Units (DAUs), a national network of DAUs from 28 universities is under formation. To assist in establishing DAUs and strengthening the network, the Swedish National Data Service and the University of Borås offer a joint professional development course to DAU staff. This course ran for the first time in spring 2018, with 21 participants from 12 universities. The course has three main objectives: to develop data management skills; to increase understanding of the institutional conditions for providing access to research data; and to strengthen the national network through interpersonal connections and collegial ties. The methodology chosen for the course is intended to promote collaboration between participants and to take into consideration their various types and levels of expertise and experience. This has resulted in a distance-learning course with four physical meetings, during which an Active Learning Classroom (ALC) methodology is used: participants work actively in groups with instructor-facilitated tasks. The ALC work is combined with significant use of collaborative work between meetings. Our presentation will show how ALC methodology can be used to support the establishment of DAUs and a DAU network. We will discuss some examples of course elements which contribute to the objectives. The discussion will be based on the facilitators’ analyses and on the participants’ answers to an evaluation questionnaire. Participants found that they developed data management skills by working with cases as ALC exercises, and thought these skills would be directly applicable to their work in the DAU. Such ALC exercises were designed around for instance anonymising datasets and writing a data management plan for a potential study. In addressing institutional conditions necessary for data access, we observed how task design and perceived relevance of a topic are important for how participants engage with various aspects of a task. For example, the ALC exercise on legal frameworks was easier to align with perceived DAU needs than the less focused and more abstract exercise on models and principles such as OAIS and FAIR. A clear outcome of the course was a strengthening of the DAU network. Participants gained a sense of collegiality by working in different constellations during various ALC tasks. The social activities – breaks and meals – intentionally included in the course also allowed classroom discussions to flow into more informal spaces. The DAUs and their national network is a vital part of the Swedish infrastructure for Open Science concerning access to research data. The presentation will end with reflections on how ALC methodology can also be employed to strengthen data management and accessibility skills in other parts of the infrastructure, for instance with researchers.